TWO NEW CHRYSOBALANACEAE OF EASTERN NEW GUINEA - a. j. g. h. kostermans (REINWARDTIA, 1984)
Hunga fusivarpa Kosterm. and Pavinari prancei Kosterm., from Milne Bay Distr., Papua-New Guinea are decribed as new species.